2018
DOI: 10.1155/2018/7834175
|View full text |Cite
|
Sign up to set email alerts
|

Novel Epigenetic Techniques Provided by the CRISPR/Cas9 System

Abstract: Epigenetics classically refers to the inheritable changes of hereditary information without perturbing DNA sequences. Understanding mechanisms of how epigenetic factors contribute to inheritable phenotype changes and cell identity will pave the way for us to understand diverse biological processes. In recent years, the emergence of CRISPR/Cas9 technology has provided us with new routes to the epigenetic field. In this review, novel epigenetic techniques utilizing the CRISPR/Cas9 system are the main contents to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 95 publications
0
38
0
2
Order By: Relevance
“…The key instruments for epigenome editing are the so-called EpiEditors, artificial proteins constructed from two functional units, one of which is responsible for the delivery of the construct to the targeted genomic region and the other for the local modification of the chromatin state to establish the desired properties. Currently, EpiEditors are mainly created using the catalytically inactive Cas9 protein (dCas9) fused to chromatin-modifying enzymes [5]. To produce a functional DNA binding unit, dCas9 needs to form a complex with a single guide RNA (sgRNA), which is designed to contain a sequence complementary to the targeted genomic locus next to a protospacer adjacent motif site ( Figure 1A) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The key instruments for epigenome editing are the so-called EpiEditors, artificial proteins constructed from two functional units, one of which is responsible for the delivery of the construct to the targeted genomic region and the other for the local modification of the chromatin state to establish the desired properties. Currently, EpiEditors are mainly created using the catalytically inactive Cas9 protein (dCas9) fused to chromatin-modifying enzymes [5]. To produce a functional DNA binding unit, dCas9 needs to form a complex with a single guide RNA (sgRNA), which is designed to contain a sequence complementary to the targeted genomic locus next to a protospacer adjacent motif site ( Figure 1A) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the correlation between epigenetics and development and progression of cervical cancer. Epigenetic modifications, such as DNA methylation, hydroxymethylation, demethylation, chromatin remodeling, histone modification, regulation by non-coding RNAs, and gene imprinting, are inheritable and affect genetic information without interfering with mitosis or meiosis (Xie et al, 2018). Among the epigenetic modifications, the role of candidate gene DNA methylation in cervical cancer has been studied the most.…”
Section: Introductionmentioning
confidence: 99%
“…A RASSF member, which contains a C-terminal RA domain and is bound to Ras, is the novel Ras effector NORE1 (RASSF5) [58]. It is interesting to note that mutations of Ras oncogenes do not play a major role in the initiation and progression of renal carcinomas [59]. This suggests that the activation of KRAS signaling may be accomplished by the inactivation of RASSF10.…”
Section: Discussionmentioning
confidence: 99%